Juridical Analysis of the Legality of Buying and Selling Inherited Assets without Permission and Approval by Some of the Legal Heirs (Case Study Decision Number: 2511K/Pdt/2020) - Purba, Mariah SM; Elpina, Elpina (Budapest International Research and Critics University, 2023)
In essence, in accordance with statutory provisions, all heirs regardless of gender and birth order are heirs to the inheritance left by the testator. However, it often happens that ownership of inherited assets is transferred, for example through buying and selling land without permission and without the knowledge of all the heirs, the transfer is only carried out by one or several heirs. The problem raised in the research is whether buying and selling inherited assets without the permission and knowledge of all the heirs is legal? Researchers were interested in conducting this research because the decision did not cancel the sale and purchase of inherited assets carried out by some of the heirs. The research method used in this research is a normative juridical legal research method, with a case study approach, namely the Supreme Court Decision with case registration Number: 2511K/Pdt/2020. The data analyzed is secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials.